Siderophore production by Gram-negative rods isolated from human polymicrobial infections - Mokracka, Joanna; Cichoszewska, Ewa; Kaznowski, Adam (Biological Letters, 2012)
A total of 137 strains isolated from 67 mixed bacterial infections were examined for production and interchangeability of siderophores. The isolates comprised 109 strains belonging to 15 species of Enterobacteriaceae and 28 isolates of 6 species of non-fermenting rods. In 36 mixed infections (53.7%), the strains secreted siderophores of the same type. This concerned mostly strains belonging to the Enterobacteriaceae (46.3%), which produced enterobactin. We selected 37 pairs of strains that produced different siderophores. The strains examined were not able to use siderophores produced by the other isolate of the pair, except for 3 strains of Pseudomonas aeruginosa that used chelators excreted by enterobactin-producing E. coli. Our research indicates that in mixed polymicrobial infections the interchangeability of siderophores is possible, although it seems to be rare. More common is the production and secretion of the same chelator by strains participating in one infection, which definitely leads to an increase in the amount of iron chelator at the site of infection and, consequently, may enhance the virulence potential of bacteria, as the amount of siderophore seems to be directly related to the pathogenicity of a strain.